EFEKTIVITAS GETAH JARAK PAGAR (Jatropha curcas) Sebagai sediaan Gel Penyembuh Luka Bakar - Nurul Pratiwi Sompah; Rini Daud Supu; Rifka Anggraini Anggai (LPPM Universitas Bina Mandiri Gorontalo, 2022)
This study aims to determine the formulation of jatropha curcas gel preparations as a burn healer, to determine the characteristics and physical properties of jatropha curcas gel preparations, and to determine theeffectiveness ofjatropha curcas gel as a burn healer. The method in this study used an experimental method with five treatments. The treatments are: P1 (4% sap), P2 (8% sap), P3 (16% sap), P4 (Negative control), and P5 (Positive Control). The results showed that the formulation of jatropha curcas gel positively contained saponin compounds that had a burn healing effect in male white rats (Rattus novergicus). Thejatropha curcas gel formulation has been shown to have a healing effect on burns of male white rats (Rattus novergicus) with a concentration of 16% providing the best healing effect with the occurrence of 100% healing (wound closure) on the third day, followed by a concentration of 8% healing (wound closure) 100% occurring on the sixth day, and a 4% concentration of 100% healing (wound closure) occurring on the ninth day.